Real-Time Car Parking System Using Arduino Control - Moshin, Ahmed Raza; Khalid, Maira; Awais, Muhammad; Ahmad, Kinza (Review of Computer Engineering Research, 2021)
In the ongoing examination of metropolitan areas, the increment in population produces high vehicle density on roads. Consequently, this prompts irritating issue for the drivers to leave their vehicles as it is hard to discover a leaving space. This paper introduces web based automatic smart parking system for vehicles. In this paper we have proposed a system which can easily manage parking system through networks of different sensors. This system can easily find a parking space and check whether the user parked the vehicle or not. In addition, this system can create unlimited locations and add slots to these locations. This is multi-user parking system where a single application can work for multiple locations. This parking system will improve the probability of successful parking and minimizes the waiting time of user. Moreover, this parking management system will encourage users to track parking slots and make the parking process a hassle-free experience.